Ancient Mesopotamia. Socio-Economic History. A Collection of Studies by Soviet Scholars (1981)
unchanged reprint of edition 1969, U.S.S.R. Academy of Sciences, Institute of the Peoples of Asia/"Nauka" Publishing House.